TEACHING ENGLISH USING ACTIVE LEARNING TECHNIQUE TO THE THIRD YEAR STUDENTS IN MI MUHAMMADIYAH PUCANG TULUNG KLATEN IN 2009/2010 ACADEMIC YEAR - RAHMAWATI, ISNA (2010)
The objective of the study is to describe the process of teaching English using Active Learning Technique, to find the strength and weakness of this technique. The result of the study is intended to be a little contribution to the teaching English. The writer formulates the problem in from of this research as follows: "how the process of teaching English using Active Learning technique and what is is the strength and weakness of using Active Learning technique". The research was done in MI Muhammadiyah Pucang, Tulung, Klaten. As the sample, the writer took 14 students of the third year. Based on the data analysis the strengths of teaching English using Active Learning technique are: (1) the students are very happy and fun; (2) they are not easy to be bored; (3) the students have the motivation to join the class and they are active in the classroom; (4) the students have a high interest in teaching-learning process; (5) it makes a good cooperation or relation among the students; (6) it makes the teacher creative. The weaknesses of teaching English using Active Learning technique are: (1) the writer must give the instruction clearly; (2) the writer needs more work preparation of Active Learning than the others technique; (3) it spends a lot of time because the writer must repeat and give the clear instructions to the students then she must guide them. The conclusion is teaching English using Active Learning technique can develop the student's knowledge in language skills including listening, speaking, reading, and writing. The students can be easy to understand, memorize, and pronounce the material given by the teacher.